KONSEKUENSI PERPAJAKAN ATAS PERUBAHAN STATUS PERSEKUTUAN KOMANDITER (COMMANDITAIRE VENNOOTSCHAP) MENJADI PERSEROAN TERBATAS - Muhammad Hasyim Ashari (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Abstract Commanditaire Vennootschap is a limited partnership business entity that is not a legal entity, while a Limited Liability Company is a legal entity that has rights and obligations as legal subjects. To increase its business, the status of a Commanditaire Vennootschap (CV) may be changed to a Limited Liability Company (PT). The purpose of this study is to identify and analyze the tax consequences arising from the change in the status of a limited partnership business entity (commanditaire vennootschap) to a limited liability company. This research is a descriptive qualitative analytical study with a library research approach, where the approach to the problem is carried out by reviewing the provisions of applicable tax regulations to determine the tax consequences of changing the status of a business entity CV to a PT. The data used in this study is secondary data using library materials / document studies. The results show that the tax consequences arising from the transition are subject to VAT (Value Added Tax) and Income Tax Final on the transfer of assets and will experience a change in Taxpayer Identification Number (NPWP) and different tax treatment between CV (Commandary Vennootschap) and PT (Limited Liability Company). Keywords: Commanditaire Vennootschap, Limited Partnership Business, Limited Liability Company, Taxation, Change of Status CV to PT.